Ketogenic diet - A gateway to optimize aerobic and anaerobic athletic performance - Dilpreet Kaur; Abdullah Alzahrani; Abdullah Alhusayni; Mohammad Ahsan; Shajiya Sarwar Moosa (Retos: Nuevas Tendencias en Educación Física, Deportes y Recreación)
This narrative review aims to highlight the effect of the Ketogenic diet on aerobic and anaerobic athletic performance. This paper adopts a narrative approach exposing the results of approximately 40 earlier studies to define the scope of applying the ketogenic diet as a nutritional therapy, aiming to aid recovery from fatigue or muscle damage caused by exercise and to increase aerobic and anaerobic performance. A ketogenic diet appears better suited for lower-intensity physical activities conducted in a balanced or moderate state of energy demand. However, there is a lack of consensus on its compatibility with strength exercises that require maximal bursts of energy. These investigations should explore its effects on performance, health, and body composition compared to other dietary approaches. Ultimately, a better understanding of the ketogenic diet's benefits and limitations will help athletes and individuals make informed decisions about its adoption for optimizing their health and athletic goals.